P.R.I.D.E, Family Institution and Development of Democratic Values in Nigeria - Azeez, Ademola (African Journal of Stability and Development (AJSD), 2018)
Nigeria’s struggle for sustainable democracy and development has, like in most other African states, been characterised by ups and downs. While no single factor can give a holistic explanation of this development, the total neglect of the roles of traditional institutions particularly the family, offers a window through which the problem can be partly understood. To be sure, there is a pervasive failure to appreciate Africa’s indigenous way of life particularly the value it places on human dignity, accountability and control, which is to a reasonable extent more democratic than the imposed alien western-liberal democracy. The attempt to reclaim the past may have informed the emphasis placed on PRIDE (P-Patriotism, Resourcefulness, I-Integrity, D[1]Distinction, E-Enterprise) by the fledgling democracy in Nigeria. The central argument of the paper is that PRIDE can strengthen family institutions in contributing to the development of social capital, which is reportedly imbued with the capabilities to develop inbuilt mechanisms for engineering the process of sustainable development especially at the grassroots level. Despite inherent limits of both the social capital theory and family institutions in Nigeria occasioned largely by the fallouts of the structural adjustment programme, there is still some sense in trying to revive African social structures particularly family institutions to reposition democratic development. Reformative efforts should therefore be targeted at the base of the problematic by trying to rejuvenate family institutions in the effective discharge of their responsibilities towards the society at large. This calls for a sustainable process of socio-political reengineering and mobilisation by all democratic stakeholders– the state, political parties, civil society, mass media, etc.